Cross-Border Property Rights and the Globalization of Innovation - Bian, Bo; Meier, Jean-Marie; Xu, Ting (Journal of Financial and Quantitative Analysis, 2025)
We identify strong cross-border property rights as a driver for the globalization of innovation. Using 67 million patents from over 100 patent offices, we construct novel measures of the three stages of innovation diffusion: adoption, sourcing, and collaboration. Exploiting staggered bilateral investment treaties (BITs) as shocks to cross-border property rights, we show that signatory countries increase technology adoption and sourcing from each other; they also increase R&D collaborations. The results are particularly strong for countries with weak domestic institutions and technologies with high imitation risks. Increases in R&D-related foreign investments explain most of the results.